Pengaruh Metode Bermain Dan Motivasi Belajar terhadap Kebugaran Jasmani Siswa Smp Pgri 4 Padang - Reffie Camelisa; Syamsuar Syamsuar; Yendrizal Yendrizal; Syahrastani Syahrastani (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem in this study, namely the lack of physical fitness of the male students of SMP PGRI 4 Padang. This study aims to see the effect of playing and motivation on physical fitness. This study uses a quasi-experimental method with a 2x2-level fakorial design. The number of samples from all treatment designs was 36 people, based on the division of the group 27% high learning motivation level and 27% low learning motivation level. Learning motivation instruments were measured by questionnaires and TKJI. The data obtained were analyzed using ANOVA and Tukey's follow-up test with a significance level of = 0.05. The final results show: (1) There is a difference between the method of playing games using tools and the method of playing games without tools on physical fitness, (2) There is no interaction between playing methods and motivation on physical fitness, (3) There is no difference in the effect of high learning motivation between the method of playing games using tools and the method of playing without tools on physical fitness, (4) In the low motivation group, games without tools are better to use the method of playing games using tools on physical fitness.